'Let's move on': second language trainee teachers' talk and its impact on learner interaction. Issue 5 (3rd September 2021) - Skinner, Barbara
ABSTRACT: Second language trainee teachers need to use effective classroom language, or 'teacher talk', otherwise opportunities for second language learning can be reduced. However, trainees are often not aware of how their teacher talk influences opportunities for language development in the classroom. This study explores teacher talk data collected from lesson transcripts of teaching practice recordings and from stimulated recall interviews with nine trainee teachers who were studying on a Teaching English to Speakers of Other Languages Master's programme at a UK university. It encourages the trainees to look up-close at their teacher talk in order to raise their awareness of its impact on second language learning. The findings of this research show that trainee teachers use teacher talk features which close down learner interaction and that this may be due to their concern with getting through and moving on with the lesson rather than with supporting learning.